2016
DOI: 10.2459/jcm.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in women with cardiovascular disease in the guidelines era

Abstract: There was no maternal or neonatal mortality and an overall acceptable incidence of cardiovascular events but a relevant percentage of pregnant were first referred late and/or for the onset of symptoms. Events were more frequent in these patients. Further efforts are needed to optimize referral to specialized centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
5
5
0
Order By: Relevance
“…We observed an overall rate of cardiac complications of 10.7%, in line with published literature reporting rates ranging from 9% to 16% 9 11 19 20…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed an overall rate of cardiac complications of 10.7%, in line with published literature reporting rates ranging from 9% to 16% 9 11 19 20…”
Section: Discussionsupporting
confidence: 90%
“…The most common adverse event found in our cohort was HF, with an overall rate of 7.1%, similarly to published data 11 19–21. Importantly, 7/14 cases of HF occurred in the first 3 days after delivery, which are characterised by the largest haemodynamic changes,22 23 with the remaining cases all within 10 days post partum.…”
Section: Discussionsupporting
confidence: 87%
“…As a consequence, the maternal mortality was quite high as compared to those in the previous studies from developed countries. 8 , 9 However, there was not much variance from that of developing countries. 12 , 13…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Italy also found high complication rates in higher classes, 5% in class I and II and 31% in class III and IV. 8 Detailed analysis of cardiovascular events found that congestive heart failure was the most common complication. This is similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation